The Effectiveness of Mental Toughness Training Ad – Menstren Model in Badminton Sports for Students of SMP Negeri 2 Jambi City (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effectiveness of mental toughness training using the Ad-Menstren mode on badminton athletes. This study uses an experimental method; in this study, there is one experimental group that is deliberately given treatment. The sample used in this study is the number of Badminton Athletes at SMP 2 Jambi City, totalling 9 students. The initial test data obtained from the initial test of the Ad-Menstren Model Mental Toughness obtained an average of 92.56, while the final test data obtained an average of 100.56. Based on the results of the normality test, the data obtained for the pre-test and post-test significance values ​​were 0.880 and 0.235 > 0.05, respectively. Based on this data analysis, it can be concluded that the pre-test and post-test data are normally distributed. The results of the analysis obtained from the t-test show significant data values ​​of 0.00 < 0.05 and the calculated T value of 3.193 > 1.8331. Based on the results of the analysis data, it can be concluded that there is a significant effect. This study concludes that there is an increase in Mental Toughness Training in Ad-Menstren Mode in Badminton Athletes at SMP Negeri 2, Jambi City.